Maria Regina Tri Yonita GAMBARAN KADAR GLUKOSA DARAH SEWAKTU PADA IBU HAMIL DI PUSKESMAS SUKARAMI KOTA PALEMBANG - Maria Regina Tri Yonita (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Background: Pregnancy is one of the factors that contribute to increased blood glucose levels. Although Gestational Diabetes Mellitus (GDM) in pregnant women is temporary, some studies show that more than 50% of pregnant women with GDM are at risk of developing type 2 diabetes, preeclampsia, eclampsia, and complications during labor which can result in overweight babies and can also be born prematurely and can even result in physical disabilities in babies. Objective: This study was to determine the picture of blood glucose levels in pregnant women at the Sukarami Health Center, Palembang City in 2025. Research Sample: totaled 30 samples. Type of Research: descriptive, and the sampling technique uses accidental sampling based on a researcher's consideration. Method: examination using POCT. Results: of 30 samples of pregnant women with elevated blood glucose levels as many as 2 samples and with normal blood glucose levels as many as 28 samples. Suggestion: to the community, especially pregnant women, it is recommended to increase knowledge information, especially about blood glucose levels in pregnant women.